Musculo-mucous web velum and velopharyngeal dysfunction associated with 8q22.1–22.2 microduplication. (January 2018) - Trudel, Mathieu; Laframboise, Rachel; Leclerc, Jacques E.
Abstract: This report presents a rare case of isolated non-cleft velopharyngeal dysfunction (VPD). An eight-year-old child presented 1. a phenotypically unique band-gap pattern of the velar musculature with anteroposterior insertion; 2. a mosaic partial trisomy on chromosome 19 as well as microduplications on chromosomes 8 and 22. Following cytogenetic analysis, microduplication on chromosome 8 was found in another member of her family. A family history of VPI with hypernasality and nasal regurgitation was reported over three different generations on the patient's maternal side. Since only one case of velum malformation is found in this family, we cannot conclude to a link between the palatal anomaly or VPD and the DNA rearrangements.